ISSUES OF ORGANIZING REMOTE AUDIT UZBEKISTAN - Yariev Sh. Sh. (Journals Park Publishing, 2025)
The article is devoted to consideration of theoretical issues of organization and development of remote audit in the Republic of Uzbekistan. Research papers and relevant statutory acts have been analyzed and appropriate conclusions and proposals have been developed.
Keywords: Financial oversight, audit, remote audit, auditing standards, ISO.